Phytoplasmas: Plant Pathogenic Bacteria - I Characterisation and Epidemiology of Phytoplasma - Associated Diseases (Springer Singapore, 2018)
Provides recent and updated information on emerging and re-emerging phytoplasma diseases affecting important crops in tropics and subtropics Provides comprehensive information on disease distribution, occurrence, and identification of the phytoplasmas Includes the recent approaches for diagnostics, transmission, and information about losses and geographical distribution along with and management aspects.